(untitled) - Senju, Shizuo (Tokyo, 1989)
This book introduce about principles for comparing alternative courses ao action. Profitability analysis considering capacitydemand relationships. Various measure for different types of selection, time value of money, selection of capital investment proposals.
Keywords: Hiệu quả chi phí,Cost effectiveness